2019
DOI: 10.19182/remvt.31516
|View full text |Cite
|
Sign up to set email alerts
|

Antibiorésistance des souches de <em>Salmonella gallinarum</em> isolées en aviculture moderne en zones périurbaines au Mali

Abstract: L’objectif de l’étude, menée d’août 2014 à décembre 2015, était de tester la résistance aux antibiotiques de 52 isolats de Salmonella gallinarum obtenus à partir d’élevages avicoles modernes situés en zones périurbaines du district de Bamako (n = 27), et des villes de Ségou (n = 16) et Sikasso (n = 9). Les taux de résistance moyens obtenus ont été de 98,08 % à l’érythromycine, 94,23 % à la colistine, 90,38 % à la streptomycine, 67,31 % à la kanamycine, 65,38 % à la fluméquine, 63,46 % à la doxycycline, 59,61 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In fact, in this study, all S. Infantis and S. Gallinarum strains were found to be resistant to the antibiotics evaluated in the aminoglycoside group (gentamicin and streptomycin). These results were similar to those reported for S. Gallinarum in Nigeria and Mali in cloacal swabs and poultry organs [43,44] and S. Infantis in Ecuador, England, and Japan in environmental samples from farms and poultry meat [12,14,45].…”
Section: Discussionsupporting
confidence: 89%
“…In fact, in this study, all S. Infantis and S. Gallinarum strains were found to be resistant to the antibiotics evaluated in the aminoglycoside group (gentamicin and streptomycin). These results were similar to those reported for S. Gallinarum in Nigeria and Mali in cloacal swabs and poultry organs [43,44] and S. Infantis in Ecuador, England, and Japan in environmental samples from farms and poultry meat [12,14,45].…”
Section: Discussionsupporting
confidence: 89%
“…The main sources of human contamination are products of avian origin, such as eggs and poultry meat [7] . The fight against avian salmonellosis in Mali is mainly based on the abusive use of antimicrobial products, in this case antibiotics [16,17] . These molecules block the growth of bacteria or destroy them.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent years have seen the spread of antimicrobial resistance among non-typhoidal Salmonella isolats in humans [8] . This antibiotic resistance represents a threat to human health and a real public health problem [16,11,5,6] . Certain strains of multi-resistant Salmonella of animal origin are suspected of having acquired their resistance genes before being transmitted to humans via the food chain [7,14] .…”
Section: Introductionmentioning
confidence: 99%
“…and Escherichia coli respectively and are considered as one of the main causes of morbidity and mortality either as a primary or secondary pathogen 2 . In West Africa, salmonellosis alone causes significant economic losses with mortalities of up to 90% 3 . Antibiotic therapy with synthetic molecules is one of the ways to control these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These include antibiotics of the tetracycline class, sulfonamides, penicillins, quinolones, aminoglycosides, polymyxins and macrolides 97,98 . The frequent use of these different classes of antibiotics has allowed over the years the emergence of multidrug resistant strains of Salmonella and Escherichia coli 3,11,13 . Thus, many authors through their work have demonstrated that several strains of Salmonella isolated from chicken farms have developed resistance to tetracyclines, sulfonamides, quinolones and polymyxins 16,99,100 .…”
mentioning
confidence: 99%